Determinants of mortality in relationship between clinical and laboratory characteristics with the outcomes of children with diphtheria: A cross-sectional study at a national hospital of Sumatra region in 2020–2023 - Dinanti, Shinta P.; Ramayani, Oke R.; Pasaribu, Ayodhia P. (Narra J, 2024)
In 2017, diphtheria outbreaks occurred in several provinces in Indonesia; however, the epidemiological data in the country is limited. The aim of this study was to determine the association between clinical findings and laboratory parameters associated with mortality of children with diphtheria. A retrospective cohort study was conducted at Haji Adam Malik General Hospital, Medan, Indonesia, covering diphtheria patients from January 2020 to December 2023. All patients aged 1–18 years clinically diagnosed with diphtheria were considered eligible. The associations between demographic characteristics, clinical features, immunization status, complications, and laboratory profiles with mortality were determined using Fisher's exact test, and the odds ratio (OR) with a 95% confidence interval (95%CI) was calculated. Our data indicated that the clinical characteristics of myocarditis (p=0.005) and airway obstruction (p=0.003) were associated with mortality. There was also a significant association between thrombocytopenia (p=0.020) and mortality in diphtheria patients. Patients with airway obstruction were 13 times more likely to have an increase in mortality compared to patients without airway obstruction. This study highlights that clinical and laboratory characteristics could be associated with in-hospital mortality of diphtheria cases, and therefore, pediatricians should be aware of the presence of those characteristics to prevent the mortality of the patients.